Experimental evaluation of yield stress-thixotropy of waste fly-ash added drilling fluid: in context with HPHT/geothermal well drilling - Satish Kumar Dewangan; Nishant Nathwani; Ajay Kawade (Journal of Engineering and Applied Science)
Abstract Proper transportation of cuttings to the surface, prevention of various well-controlled issues, stability of wellbore, formation damage minimization, etc. are very important issues that depend crucially on properly designed and maintained rheology of the drilling fluids. Search and selection of suitable drilling fluid additives that can favorably alter its rheology has always been a challenge for oilwell drilling industries. On the other hand, disposal of fly ash, which is a waste of thermal power industries is a big time issue to resolve considering these two important aspects, i.e., drilling fluid rheology investigation as well as suitable disposal outlet of fly ash, the present analysis was aimed to investigate the effective application of fly-ash (a waste of thermal power plants) as possible favorable rheology altering additives of water-based drilling fluids for wellbore drilling industries. Various drilling fluid samples based on fly ash were prepared and experimentally tested for their yield stress and thixotropic behavior. Rotational rheometer MCR-102 (Make: Anton-Paar) was used for the rheological analysis. The investigation compared different drilling fluid combinations based on fly ash and oil additives. Various time-dependent rheological aspects, i.e., thixotropic characteristics like thixotropic area, loss modulus, and damping coefficient were experimentally explored. Additionally, yield shear stress values were investigated by controlled shear stress tests with MCR-102. At the outset, the comprehensive thixotropic analysis concluded that nearly 10% of the fly ash addition would optimally be beneficial to sustain the favorable yield-thixotropy to water-based drilling fluids. It was also concluded that fly ash addition did not affect the chemical reactivity of the drilling fluid. All the samples exhibited the desired shear thinning behavior. The damping factor was greater than unity which implied the dissipative nature of all the drilling fluid samples, however presence of oil in the sample reduced it.